Dating Satisfaction in young adults according to their sexual orientation in Merida, Yucatan - Cahuich Lemus, Génesis (Consorcio de Universidades Mexicanas A.C., 2013)
Heterosexual relationships have been more accepted than homosexual orientation, however, it cannot be ignored the existence of the latter in a dating relationship. This research seeks to establish if there is a relationship between dating satisfaction, depending on sexual orientation and gender, in a group of young adults. The Multidimensional scale of dating satisfaction of Bargas and Garcia (2011) composed of 11 dimensions was used. The sample consisted of 90 participants from 18 to 30 years of which 44 were men and 46 women. In terms of sexual orientation, 47 claimed to be heterosexual, and 43 with a different sexual orientation. Results showed that, according to sexual orientation and dating satisfaction, people with heterosexual orientation are the most satisfied in the familiar interaction dimensions than another sexual orientation. With respect to satisfaction of men and women regardless of their sexual orientation, the results suggest that men are happier than women regarding to the time spent together and shared activities, and women are more satisfied concerning to the interaction with their partner’s friends, in making decisions, agreements, and communication with the couple. It is discussed the influence of family on dating relationships since the absence of acceptance could cause family distancing and it may affect the couple’s satisfaction.